2012
DOI: 10.1096/fj.12-207431
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction

Abstract: The epithelial sodium channel (ENaC) is responsible for Na+ and fluid absorption across colon, kidney, and airway epithelia. We have previously identified SPLUNC1 as an autocrine inhibitor of ENaC. We have now located the ENaC inhibitory domain of SPLUNC1 to SPLUNC1's N terminus, and a peptide corresponding to this domain, G22-A39, inhibited ENaC activity to a similar degree as full-length SPLUNC1 (∼2.5 fold). However, G22-A39 had no effect on the structurally related acid-sensing ion channels, indicating spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been established previously that the N-terminal S18 region of SPLUNC1 inhibits the epithelium sodium channel (ENaC), reducing the influx of sodium and water into pulmonary epithelial cells and maintaining the height of the airway surface liquid. 5,6 We found that the Δα4, LA x 4 and M3+LA x 4 forms of human SPLUNC1 were not significantly different from SPLUNC1 in ASL height (Fig. 4A).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been established previously that the N-terminal S18 region of SPLUNC1 inhibits the epithelium sodium channel (ENaC), reducing the influx of sodium and water into pulmonary epithelial cells and maintaining the height of the airway surface liquid. 5,6 We found that the Δα4, LA x 4 and M3+LA x 4 forms of human SPLUNC1 were not significantly different from SPLUNC1 in ASL height (Fig. 4A).…”
Section: Discussionmentioning
confidence: 87%
“…In the context of cystic fibrosis (CF) inactivating mutations of the CFTR channel, ENaC’s actions exacerbate the dehydration of CF pulmonary tissues. 5 Eighteen amino acids in the N-terminal region of SPLUNC1 (S18) were found to be necessary and sufficient for regulating ENaC in normal conditions in vitro ; however, in the low pH of CF tissues, both S18 and the body of SPLUNC1 were required to control ENaC. 6 SPLUNC1 has also been shown to act as a surfactant to spread fluids at the air-water interface, and an innate antibacterial factor against Gram-negative bacterial pathogens.…”
mentioning
confidence: 99%
“…In the current study, we focused on the effects of HNE on the function of a recently described host defense protein short palate, lung, and nasal epithelium clone 1 (SPLUNC1). A previous study suggests that HNE is involved in SPLUNC1 degradation [11]. However, the role of HNE-mediated SPLUNC1 degradation in host defense against bacterial infection has not been investigated.…”
Section: Introductionmentioning
confidence: 99%